2017
DOI: 10.1002/lary.26662
|View full text |Cite
|
Sign up to set email alerts
|

Systemic bevacizumab for recurrent respiratory papillomatosis: A national survey

Abstract: Objective Aggressive laryngeal, tracheal and pulmonary papilloma is an extremely challenging clinical problem without proven treatment options. A recent German report documented promising results with systemic bevacizumab. The objective of this study is to report the initial experience of this novel treatment in the United States for Recurrent Respiratory Papillomatosis (RRP). Study Design Cases series Methods Electronic survey of the RRP Task Force of the American Society of Pediatric Otolaryngology, Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 9 publications
1
86
0
3
Order By: Relevance
“…Only three reports on the use of systemic bevacizumab in children have been published (Table I). The authors observed satisfactory results, with a reduction in the need for surgery, improvement of quality of life, 6,7,9 with no severe toxicity. However, it is important to note that all of the studies were small, with limited treatment duration and short follow-up.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Only three reports on the use of systemic bevacizumab in children have been published (Table I). The authors observed satisfactory results, with a reduction in the need for surgery, improvement of quality of life, 6,7,9 with no severe toxicity. However, it is important to note that all of the studies were small, with limited treatment duration and short follow-up.…”
Section: Discussionmentioning
confidence: 90%
“…Bevacizumab has no effect on the viral DNA and mechanisms of apoptosis, but presents a direct antiangiogenic action that affects tumor growth 9 and is responsible for the therapeutic effect. 9 It is responsible for reduction of the lesions' size and the improvement of airway permeability, without eradicating the viral infection and risk of recurrence after suspending the treatment. On the first patient, we used a 10-mg/kg dosing schedule, which is recommended for adults in most case reports published in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising adjuvant pharmacological agent is bevacizumab -a recombinant monoclonal humanized antibody -that blocks angiogenesis by inhibiting the human vascular endothelial growth factor A (VEGF-A), which has been shown to play an important role in the pathogenesis of RRP (14). Several recent studies have demonstrated its satisfactory results by decreasing the growth of papillomatous lesions and prolonging intervals between the surgical procedures (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Auch im In-vitro-Versuch zeigt sich eine erhöhte Kanzerogenität des Medikaments, sodass die Therapie trotz vielversprechender Ansprechraten kontrovers diskutiert wird [42]. Erste klinische Arbeiten zu dieser Therapie zeigen vielversprechende Ansprechraten mit Verlängerung der Therapieintervalle und partiellen sowie zum Teil auch kompletten Remissionen [43,44]. Der Antikörper wird sowohl lokal injiziert als auch bei schweren Verläufen systemisch verabreicht.…”
Section: Therapieunclassified